CHARACTERIZATION OF REFUSE DERIVED FUEL (RDF) PELLETS IN THE MUNICIPAL SOLID WASTE PROCESSING PROCESS - Dewi, Rany Puspita; Saputra , Trisma Jaya; Fajarningrum , Nurmala Dyah; Agung, Hidayat (Jurnal Rekayasa Mesin, 2025)
Municipal Solid Waste (MSW) can be processed to be Refuse Derived Fuel (RDF) pellets. Generally, RDF is combustible waste that processed by crushing and filtering through converting it to solid fuel. RDF pellets can be made by pressing using a pellet machine names pelletizer. The research goal was to analyze the characterization of RDF pellets processing by pelletizer. The characterization tested includes calorific value and water content. The research was done by varying the composition of waste that are sample A (70% organic + 30% inorganic), sample B (60% organic + 40% inorganic), sample C (50% organic + 50% inorganic), sample D (40% organic + 60% inorganic), and sample E (30% organic + 70% inorganic). The research results showed that the highest calorific value was obtained in sample E, 4199,2754 cal/g and the lowest water content was obtained in sample E, 23,0416%.